Cash Management System, Is It Increase Transparancy? - Rusmiyatun Rusmiyatun; Anna Probowati; M Azizul Islam (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2023)
This research aims to determine the effectiveness of implementing a cash management system . Cash Management system is a transformation of non-cash payments that is implemented. The respondents of this research were 458 schools in Purworejo Regency. The analysis uses a qualitative descriptive analysis method by distributing questionnaires to cash management system holders. The research results show that CMS can increase the transparency of financial management and regular monitoring by leaders for school financial management. with the implementation of CMS on payment methods, it makes it easier for treasurers not to hold money in cash and to pay for activities non-cash. The payment track record is also listed in the bank statement which can be accessed at any time.